2016
DOI: 10.1016/j.chb.2016.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Interactivity and memory: Information processing of interactive versus non-interactive content

Abstract: a b s t r a c tExisting research on the effects of interactivity tends to treat it as a global characteristic of the interface. However, not all content on an interface is endowed with interactive features. Therefore, it is important to explore how interactivity affects the cognitive processing of those particular content that is presented with interactive features and the surrounding content without these features. With this objective, a between-subjects experiment was conducted to understand how levels of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
(58 reference statements)
5
41
0
Order By: Relevance
“…Similar to the results of our study, Xu and Sunder [60] reported that interactivity encourages the processing of interactive content and compromises the processing of non-interactive content. In our study, user involvement with the content in Swipe, Checkbox, and DAD groups does not cover all the content but only the requested data and the data processing purposes.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the results of our study, Xu and Sunder [60] reported that interactivity encourages the processing of interactive content and compromises the processing of non-interactive content. In our study, user involvement with the content in Swipe, Checkbox, and DAD groups does not cover all the content but only the requested data and the data processing purposes.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding memory for story content, the results point to the latter: participants reported significantly lower levels of knowledge acquisition after reading a news text including a 360-degree photograph than after reading text alone. This finding indicates that the immersive image served as a distractor, seducing news consumers' attention away from the actual story (Van Damme et al, 2018), and depriving them of cognitive resources they would have needed to thoroughly attend, process, and store the information presented in the accompanying news article (Xu & Sundar, 2016). Since dragging around an omnidirectional image is considered a rather easy task, it is plausible that participants might had enough mental resources left for storing information (Boksem, Meijman, & Lorist, 2005), but simply lacked the motivation to carefully attend them.…”
Section: Discussionmentioning
confidence: 99%
“…Within this theoretical perspective, immersive media such as 360-degree photographs are viewed as complex stimuli that are difficult for individuals to encode, thereby tying up their limited cognitive resources and leaving insufficient capacities for the storage and retrieval of information (Xu & Sundar, 2016). Following Bucy (2004), it is assumed that enabling recipients to freely explore an omnidirectional shot generates higher levels of involvement, but at the same time over-stimulates the human information processing system.…”
Section: Effects On Information Processing and Knowledge Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work points out that when a website is more interactive, it can also increase absorption into the reading (Oh & Sundar, 2015), which has positive effects on information processing, and may even lead to higher favorability toward the content (Sicilia, Ruiz, & Munuera, 2005), and to higher recall and recognition (Xu & Sundar, 2016). Thus, research has shown that if a website is more interactive (e.g., contains more hyperlinks and requires more interaction from its users), citizens engage in more cognitive elaboration (i.e., making connections between news information and previous knowledge), which leads to increased recall of content (Tremayne & Dunwoody, 2001).…”
Section: Linearity Of Usementioning
confidence: 99%